What do you say after you say hello? : the psychology of human destiny - Berne, Eric, 1910-1970 (Grove Press, 1972)
As a psychiatrist, Dr. Berne found that each person, in early childhood--under the powerful influence of his parents--writes his own script that will determine the general course of his life. That script dictates what kind of person he will marry, how many children he will have, even what kind of bed he will die in. Most of all, it determines whether he will be a winner or a loser, a spendthrift or a skinflint, a tower of strength or a doomed alcoholic. Some people, says Berne, have scripts that call for them to fail in their professions, or to be repeatedly disappointed in love, or to be chronic invalids. Here, he demonstrates how each life script gets written, how it works, and how each of us can break free of it to help us attain real autonomy and true fulfillment.--From publisher description.